Sexism in Social Media Comments: The Case of the X Account @txtdarifeminis - Indasah, Kurnia (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
This study aims to map the typology and characteristics of sexist messages appearing in netizen comments on the X account (formerly Twitter) @txtdarifeminis, which actively reframes feminist narratives negatively as jokes or attacks. Despite the development of gender studies in Indonesia, a significant research gap remains because the dominant literature remains focused on mainstream media products. This study offers novelty by filling this gap through the analysis of user-generated content, where sexism is produced collectively and participatively. Using a qualitative content analysis approach within a constructivist paradigm, data were collected using data mining techniques in RStudio and the rtweet package. Of the 1,151 tweets collected, 106 were purposively selected as the primary unit of analysis. The research findings identified eight main dominant variants of sexism: (1) verbal demeaning of women; (2) constructing women as passive; (3) sexual objectification; (4) misconceptions and distortions of the feminist agenda; (5) negative stereotypical labeling of feminists; (6) justification of the domestication of women's roles; (7) glorification of masculine superiority; and (8) symbolic threats or punishments for women who violate norms. This study contributes to the study of gender communication by presenting a typology of sexism in the local context and offering practical recommendations for developing more inclusive content moderation and digital literacy policies.